2020
DOI: 10.1145/3362168
|View full text |Cite
|
Sign up to set email alerts
|

Decentralized Trust Management

Abstract: Decentralized trust management is used as a referral benchmark for assisting decision making by human or intelligence machines in open collaborative systems. During any given period of time, each participant may only interact with a few of other participants. Simply relying on direct trust may frequently resort to random team formation. Thus, trust aggregation becomes critical. It can leverage decentralized trust management to learn about indirect trust of every participant based on past transaction experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 88 publications
0
1
0
1
Order By: Relevance
“…the literature. Additionally, older studies[31,27] considered that trust models keep leveraging static thresholds instead of dynamic ones in the model decision making.Following this analysis, it can be concluded that the field of TMM matured in time, has clear definitions and terminology[5,34,6], methods and algorithms[31,32,30,29], and scope in terms of trust collaboration, threats and threat models[27,12,31,11]. Additionally, a pattern frequently observed after breaking down the studies in chronological order, is that the same open issues and gaps are still found and mentioned,VOLUME 11, 2023 …”
mentioning
confidence: 78%
See 1 more Smart Citation
“…the literature. Additionally, older studies[31,27] considered that trust models keep leveraging static thresholds instead of dynamic ones in the model decision making.Following this analysis, it can be concluded that the field of TMM matured in time, has clear definitions and terminology[5,34,6], methods and algorithms[31,32,30,29], and scope in terms of trust collaboration, threats and threat models[27,12,31,11]. Additionally, a pattern frequently observed after breaking down the studies in chronological order, is that the same open issues and gaps are still found and mentioned,VOLUME 11, 2023 …”
mentioning
confidence: 78%
“…Our motivation relies on the significant amount of research papers published in the field of TMM, making it of crucial importance to systematise and review the acquired academic knowledge. Multiple previous works [12,6,13,7] already paved the road for a better understanding of how trust is measured, modelled and managed in complex DWNs. Con-sequently, the present work aims to explore and expand this effort through the following contributions:…”
mentioning
confidence: 99%
“…Alternatively, secure lightweight multi-factor authentication protocols which are offered as a service [13], [59] are more realistic solutions in a smart farming network environment. In fact, an intermediary Certifying Authority (CA) can facilitate the authentication of a connecting device [60]. Such authentication mechanisms do not consume devices' limited resources for authentication processing, but also unauthorized devices will be prevented from connecting and accessing the network in an efficient way [61].…”
Section: Authentication and Secure Communicationmentioning
confidence: 99%
“…信誉值动态更新函数计算如下: [16] 和 ReMSA [17] 中的 信誉聚合算法得到的 AS9498 信誉评价, 如图 5 所示. [30] 提出了 EigenTrust++ [31] , GroupTrust [32] 等方 案. 这些方法引入基于节点直接信誉评价相似度的节点信誉评价可采信度评估、设置信誉传播阈值控 制信誉聚合传播等措施, 以阻止不合理的信誉传播.…”
Section: 信誉评价动态更新unclassified